Development of Digital Learning Media Pantun Melayu For High School Students to Improve The Competence of Literary Appreciation - Elmustian Elmustian; Siti Andriana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This article discusses the development of Digital Learning media based on Malay rhymes for high school students (SMA) with the aim of improving the competence of literary appreciation. The research was conducted using research and Development (R & D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observation, questionnaires, and literature appreciation tests given to students before and after using digital learning media. The results showed that digital learning media Malay poem was able to improve students' understanding of the structure, meaning, and cultural values in the poem. In addition, this media makes it easier for teachers to present literary material in an interactive and interesting way, thereby increasing student learning motivation. The integration of digital media in learning also facilitates students in exploring literature more creatively. This finding confirms that the integration of digital technology in traditional literary learning can support the improvement of cultural literacy competence and literary appreciation in high school students. This innovation opens up new possibilities for engaging students with their cultural heritage in a digital era, encouraging a deeper understanding and connection with traditional arts.